Solitary plasmacytoma: A case report - Guruvelli, Sandya Rani Padma; Gangadharan, Vandana; Prakash, S Sri Krishna; Atla, Bhagyalakshmi (Indian Journal of Case Reports, 2024)
Plasmacytoma is a discrete, unifocal, and monoclonal neoplastic proliferation of plasma cells. It may present as one of the three distinct clinical entities: multiple myeloma (MM), solitary plasmacytoma of the bone, and extramedullary plasmacytoma. Solitary plasmacytoma of the bone accounts for 3% of all plasma cell neoplasms. About 50% of the cases of solitary plasmacytoma of the bone transform into MM. The most commonly involved sites are vertebrae and long bones. It is extremely rare in jaws. We are presenting a case of solitary plasmacytoma of the maxilla in a 59-year-old female patient with comprehensive clinical, radiological, histological, and immunohistochemical features.